Sustainable Resin Collection and trade Practices in Mid Hills of Nepal - Gotame, Bharat (The Initiation, 2014)
Non Timber Forest Products (NTFPs) in mountains are one of the enormously valued ecosystem services due to their contribution to the livelihood of people. Pine resin is one of the viable NTFP in middle mountain of Nepal which is tapped from Pinus roxbhurghii tree and can be used in paints, varnishes, stimulant, anti-spasmodic, astringent, diuretic and anti-pathogenic and so on. This piece of work is an attempt to review the current status of pine resin collection enterprise in Nepalese Community Forests and its contribution to the livelihood of Community forest users in mid-hill region. Typically, existing legislations and guidelines have high potential to endure the sustainable livelihood promotion by resin tapping enterprise but the endeavors of revitalizing the financial benefit sharing and governance system is still far. The valued contribution of resin enterprise to sustainable livelihood of users is not impossible but it needs greater effort of all stakeholders. For example, partial intervention to market, involvement of poorer households, improve the local and regional governance and so on. Participatory monitoring of collection work and proper enforcement of sustainable harvesting procedure both have to be improved in state of arts that could finally recognize the rational benefit sharing mechanism among various value chain actors from collector to international traders which is indispensable. DOI: http://dx.doi.org/10.3126/init.v5i0.10262 The Initiation 2013 Vol.5; 128-137